Verification of the code DYN3D for calculations of neutron flux fluctuations. (February 2022) - Viebach, M.; Lange, C.; Kliem, S.; Demazière, C.; Rohde, U.; Hennig, D.; Hurtado, A.
Highlights: Investigation of applicability of the reactor dynamics code DYN3D for neutron noise Comparision of DYN3D against 1D analytic references and 3D CORE SIM references Maximum deviations from the reference solutions in the range between 0.005% and 6% Abstract: Insufficiently explained magnitudes and patterns of flux fluctuation observed mainly in KWU PWRs are recently investigated by various European institutions. Among the numerical tools used to investigate the neutron flux fluctuations is the time-domain reactor dynamics code DYN3D . As DYN3D and comparable codes have not been developed with the primary intention to simulate low-amplitude neutron flux fluctuations, their applicability in this field has to be verified. In order to contribute to the verification of DYN3D for the simulation of neutron flux fluctuations, two special cases of perturbations of the neutron flux (a localized absorber of variable/oscillatory strength and a travelling oscillatory perturbation) are considered with DYN3D on the one hand and with the frequency-domain neutron noise tool CORE SIM as well as analytical frequency-domain approaches, respectively, on the other hand. The obtained results are compared with respect to the distributions of the amplitude and the phase of the induced neutron flux fluctuations. The comparisons are repeated with varied amplitudes and frequencies of the perturbation. The results agree well both qualitatively and quantitatively for each of the conducted calculations. The remaining deviations between the DYN3D results and the reference results exhibit a dependence on the perturbation magnitude, which is attributed to the neglect of higher-order terms (linear theory) of the perturbed quantities in the calculation of the reference solutions.